JOINT MESSAGE FROM THE ORNAC PRESIDENT AND EXECUTIVE DIRECTOR - Khotar, Rupinder; Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2013)
It is with great pleasure that we bring you this joint message about the implementation of the ORNAC Strategic Plan and some of the initiatives and activities that are making ORNAC an even more dynamic association. The ORNAC Board of Directors has been busy planning future initiatives for ORNAC and bringing added value to ORNAC members. In this message we share updates on some of the initiatives.